Liczby, dane i statystyki w dziennikarstwie internetowym - Szews, Przemysław (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
In today’s era, in which visual communication and multimedia dominate, a direct result of this has been the development of genres based on the visual transfer of information. The visualisation of information connects the communicative goals of a journalist with the reader’s expectations. Infographics, which combine a graphic representation of information with an understandable, dynamic and updated form of presentation is becoming a crucial form of informative discourse. This form can be an element that enriches a text, but it can also function as an autonomous journalistic genre, with its own categories and varieties. Data journalism, i.e., journalism based on figures and statistics, is very closely connected with infographics; its aim is the collecting, filtering and interpreting of data (e.g. by means of infographics). Thus, the skill of storing data is becoming very important in a journalist’s work, comparably important to interpretation and presentation. Figures, percentages and statistics are significant sources of information, as well as means of telling and creating a story. They may also be used as a source of entertainment and a means of engaging the reader; the phenomenon of “datatainment” (derived from sport), meaning the use of data for the sake of provoking a reader’s interaction, provides proof of this.